Experimental Study of the Effect of Fuel Type on the Emitted Emissions from SIE at Idle Period - Miqdam T. Chaichan (Al-Khwarizmi College of Engineering – University of Baghdad, 2018)
The present study investigated the impact of fuel kind on the emitted emissions at the idling period. Three types of available fuels in Iraq were tested. The tests conducted on ordinary gasoline with an octane number of 82, premium gasoline with an octane number of 92, and M20 (consist of 20% methanol and 80% regular gasoline). The 2 liters Mercedes-Benz engine was used in the experiments.